2017
DOI: 10.12973/eurasia.2017.01235a
|View full text |Cite
|
Sign up to set email alerts
|

Context of STEM Integration in Schools: Views from In-service Science Teachers

Abstract: This study explores science teachers' views regarding Science, Technology, Engineering and Mathematics (STEM) pedagogy and its interdisciplinary nature. It also seeks to identify teachers' views on the contextual factors that facilitate and hinder such pedagogy in their schools. Qualitative methodologies were used through focus group discussions and an interview protocol. From the specific contextual issues that were highlighted in the findings, was teacher self-efficacy, pedagogical-knowledge, issues related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 22 publications
(26 reference statements)
5
80
0
6
Order By: Relevance
“…The same teachers felt collaboration and technology would be important to transdisciplinary teaching. The concept of interdisciplinarity was difficult for some secondary teachers to grasp, with a perception that integration between two subjects was possible but putting the four STEM disciplines together was problematic (El-Deghaidy et al 2017). El-Deghaidy et al (2017) also found the teachers did not have a clear understanding of how to integrate technology, believing it was just hardware.…”
Section: Cross-curricular Integrationmentioning
confidence: 99%
See 4 more Smart Citations
“…The same teachers felt collaboration and technology would be important to transdisciplinary teaching. The concept of interdisciplinarity was difficult for some secondary teachers to grasp, with a perception that integration between two subjects was possible but putting the four STEM disciplines together was problematic (El-Deghaidy et al 2017). El-Deghaidy et al (2017) also found the teachers did not have a clear understanding of how to integrate technology, believing it was just hardware.…”
Section: Cross-curricular Integrationmentioning
confidence: 99%
“…Teachers value these authentic learning experiences, without one right answer (Bruce-Davis et al 2014). They felt students needed lots of practice participating in group work and learning through doing in order to be successful with STEM learning (El-Deghaidy et al 2017;Herro and Quigley 2017). Several teachers were happily surprised that low-performing students were able to be successful in the less-structured and more challenging STEM problems (Lesseig et al 2016;Wang et al 2011).…”
Section: Student Strugglesmentioning
confidence: 99%
See 3 more Smart Citations